Enhancement of antiviral capacity of transgenic silkworms against cytoplasmic polyhedrosis virus via knockdown of multiple viral genes. (December 2017) - Jiang, Liang; Peng, Zhengwen; Guo, Huizhen; Sun, Jingchen; Sun, Qiang; Xia, Fei; Huang, Chunlin; Xu, Guowen; Xia, Qingyou
Abstract: Bombyx mori cytoplasmic polyhedrosis virus (BmCPV), a major pathogen of silkworms, causes serious economic losses in sericulture. The BmCPV genome contains 10 discrete dsRNA segments; among these, S1, S2, S3, S4, S6, and S7 encode virus structural proteins, whereas S5, S8, S9, and S10 encode nonstructural proteins. In an attempt to create an anti-BmCPV silkworm strain, we constructed transgenic RNAi vector pb-CNS for knockdown of S5, S8, S9, and S10, and pb-SNS targeting S1, S2, S4, S5, and S8. Transgenic silkworm line CNS and SNS were generated via microinjection of the practical diapause silkworm strain Furong. Following infection via the oral administration of a high dose of BmCPV, the mortality rates of the nontransgenic control, CNS, and SNS were 91%, 37%, and 41%, respectively. qPCR showed that the viral mRNA content in CNS and SNS was significantly lower than that in the nontransgenic line. The economic traits of CNS and SNS were not affected. These results suggest that the knockdown of multiple BmCPV genes significantly enhances the antiviral capacity of the silkworm. Highlights: Nonstructural protein-encoding genes S5, S8, S9, and S10 of BmCPV in transgenic silkworm CNS were knocked down by RNAi. Structural (S1, S2, S4) and nonstructural (S5, S8) protein-encoding genes in transgenic silkworm SNS were silenced by RNAi. The mortality rates of CNS and SNS were 54% and 50% lower than those of the control following infection with high-dose BmCPV. The economic traits of transgenic CNS and SNS were unaffected.